HAK CUTI HAID DALAM PERSPEKTIF HUKUM KETENAGAKERJAAN - Ardini, Mira; Fatriany, Fenny (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
Undang-Undang Nomor 13 Tahun 2003 tentang Ketenagakerjaan regulates the right to access employment, including specific provisions for women. However, the implementation of these regulations in practice remains suboptimal. Menstrual leave rights are often considered insignificant by labor unions, making them rarely advocated. This study aims to examine the regulation of menstrual leave rights in the Undang-Undang Ketenagakerjaan and to compare the gaps between the existing regulations and their implementation. The findings and discussions reveal a discrepancy between the provisions of the Undang-Undang Ketenagakerjaan and their actual application in the field. For instance, at PT. Asera Tirta Posidonia, the majority of female workers are unaware of their rights regarding menstrual leave. Therefore, concrete steps are needed to bridge this gap. The government must strengthen oversight of the implementation of the Undang-Undang Ketenagakerjaan, particularly concerning menstrual leave rights, and companies should actively disseminate information to female workers about their rights.